The river - Godden, Rumer 1907-1998; Partha Sarathy, M.A (<<The>> Criterion Coll., 2005)
An English family lives in Bengal, India, which provides the backdrop for the coming-of-age story of Harriet, the heroine, an adolescent girl who experiences the first pangs of womanhood when she falls in love with a wounded American war hero, loses a beloved family member, and begins to express her deepest feeling in eloquent verse.
Bildformat: 1.33:1 aspect ratio. - New, high-definition digital transfer from the 2004 film restoration
Orig.: USA, Indien, Frankreich 1951
Enth. Introduction to the film by Jean Renoir. - "Rumer Godden: An Indian Affair", a 1995 BBC documentary that follows the author as she journeys back to her childhood home in India. - New video interview with Martin Scorsese, a key figure in the restoration. - 2000 audio interview with producer Ken McEldowney. - Stills gallery featuring production photos and publicity stills. - Essays by film scholars Ian Christie and Alexander Sesonske
Keywords: Feature films; Indien; India -- Social conditions -- Drama